Biodiversity and Classification of Phages Infecting Lactobacillus brevis - Feyereisen, Marine; Mahony, Jennifer; Neve, Horst; Franz, Charles M. A. P.; Noben, Jean-Paul; O’Sullivan, Tadhg; Boer, Viktor; van Sinderen, Douwe (Frontiers in Microbiology, 2019)
Lactobacillus brevis is a lactic acid bacterium that is known as a food and beverage spoilage organism, and more specifically as a beer-spoiler. Phages of Lb. brevis have been described, but very limited data is available regarding temperate phages of Lb. brevis. Temperate phages may exert benefits to the host, while they may also be employed to combat beer spoilage. The current study reports on the incidence of prophage sequences present in nineteen distinct Lb. brevis genomes. Prophage induction was evaluated using mitomycin C exposure followed by genome targeted-PCR, electron microscopy and structural proteome analysis. The morphological and genome sequence analyses revealed significant diversity among Lb. brevis (pro)phages, which appear to be dominated by members of the Myoviridae phage family. Based on this analysis, we propose a classification of Lactobacillus brevis phages into five groups.